2019
DOI: 10.1163/15700682-12341453
|View full text |Cite
|
Sign up to set email alerts
|

Buddha as a God: An Empirical Assessment

Abstract: For at least a century, scholars have argued about whether or not Buddha is considered a god. We treat this question empirically by conducting two ethnographic studies among residents of the Tyva Republic, one of the Buddhist republics in the Russian Federation. Using a mixed methods approach to interrogate the question, this report concludes that Buddha is, in fact, popularly represented as a punitive and moralistic supernatural agent in the republic and demographic factors co-vary with such beliefs. The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Buddhism is also diverse, and while many traditions do not require or even encourage belief in gods or other supernatural agents, many individual Buddhists do believe that the world is inhabited by a variety of supernatural agents worthy of respect and devotion, and some ascribe to Buddha many of the omniscient, punitive, moralistic traits that characterize gods (Berniūnas et al, 2020; Purzycki & Holland, 2018; Stanford & Jong, 2019). In contrast, karma is typically characterized as the consequences for one's actions that are unrelated to divine intervention (Bronkhorst, 2011; Gowans, 2014; Willard, Baimel, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Buddhism is also diverse, and while many traditions do not require or even encourage belief in gods or other supernatural agents, many individual Buddhists do believe that the world is inhabited by a variety of supernatural agents worthy of respect and devotion, and some ascribe to Buddha many of the omniscient, punitive, moralistic traits that characterize gods (Berniūnas et al, 2020; Purzycki & Holland, 2018; Stanford & Jong, 2019). In contrast, karma is typically characterized as the consequences for one's actions that are unrelated to divine intervention (Bronkhorst, 2011; Gowans, 2014; Willard, Baimel, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Buddhism is also diverse, and while many traditions do not require or even encourage belief in gods or other supernatural agents, many individual Buddhists do believe that the world is inhabited by a variety of supernatural agents worthy of respect and devotion, and some ascribe to Buddha many of the omniscient, punitive, moralistic traits that characterize gods (Berniūnas et al, 2020;Purzycki & Holland, 2018;Stanford & Jong, 2019). In contrast, karma is typically characterized as the consequences for one's actions that are unrelated to divine intervention (Bronkhorst, 2011;Gowans, 2014;Willard, Baimel, et al, 2020).…”
Section: Do Intuitions Also Predict Belief In Karma?mentioning
confidence: 99%
“…The expectation that what goes around comes around-that virtuous people are rewarded for their prosociality and hard work, and bad people are punished for their misdeeds-is a hallmark of norms in interpersonal relationships and, for many people, this reciprocity also characterizes the universe more broadly, through the intervention of supernatural entities. The belief in supernaturally-enforced consequences for norm violations is widespread around the world, but comes in many varieties, including gods, ancestral or nature spirits, witches and sorcerers and demons, non-agentic forces like karma, and an afterlife determined by one's actions on earth (D. Johnson, 2015;Purzycki, 2013;Purzycki et al, 2016;Purzycki & Holland, 2018;Singh, 2020;.…”
Section: Karma and God: Convergent And Divergent Mental Representations Of Supernatural Norm Enforcementmentioning
confidence: 99%
“…In recent cross-cultural studies sampling from a significant portion of global variability in religious beliefs and in social complexity, curbing interpersonal transgressions emerged as a central feature to descriptions of moralizing gods' desires (Lang, Purzycki, Apicella, Atkinson, Alexander, et al, 2019;Purzycki et al, 2016Purzycki et al, , 2012Purzycki & Holland, 2018); in turn, commitment to these gods was found to be related to greater impartiality towards coreligionist strangers in these samples (Lang et al, 2019;Purzycki et al, 2016). Recent research supports a broad association between supernatural punishment beliefs and prosociality, which is not limited to belief in gods per se.…”
Section: Similarities In Belief In God and Karma In Relation To Interpersonal Moralitymentioning
confidence: 99%
See 1 more Smart Citation